Low temperature synthesis of nano alpha-alumina powder by two-step hydrolysis. (January 2016) - yan, Ting; Guo, Xiaode; Zhang, Xiang; Wang, Zhixiang; Shi, Jinqiu
Graphical abstract: Highlights: The nano α-Al2 O3 with good dispersion was prepared by two-step hydrolysis. α-Al2 O3 powders were added as seed particles in the hydrolysis. This article indicated that the glucose could impel the γ-Al2 O3 transformed to α-Al2 O3 directly. This article indicated that the addictive of α-Al2 O3 seed could improve the phase transformation rate of γ-Al2 O3 to α-Al2 O3 . In this article, the pure α-Al2 O3 could be obtained by calcining at 1000 °C for 1.5 h. Abstract: The ultral fine alpha-alumina powder has been successfully synthesized via two-step hydrolysis of aluminum isopropoxide. Glucose and polyvinyl pyrrolidone were used as surfactants during the appropriate processing step. The alpha-alumina powder was used as seed particles. Several synthesis parameters, such as the amount of seeds, surfactants, and calcination temperature, were studied by X-ray diffraction (XRD), Fourier transform infrared spectra (FTIR), Thermogravimetry-differential scanning calorimetry (TG-DSC), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The experimental results showed that glucose greatly lower the phase transformation temperature of alpha-alumina by impelling the gamma-alumina transformed to alpha-alumina directly, and the seed could improve the phase transformation rate of alpha-alumina, the polyvinylpyrrolidone have an effect on preventing excessive grain growth and agglomeration of alpha-alumina powder. Comparatively well dispersed alpha-alumina powder with particle size less than 50 nm can be synthesized through this method after calcinations at 1000 °C for 2 h.